Structure-dependent immune modulating activity of okra polysaccharide on THP-1 macrophages. (January 2019) - Trakoolpolpruek, Thanathon; Moonmangmee, Somporn; Chanput, Wasaporn
Abstract: Polysaccharides from various plants exhibit immune modulating activity directly through immune cell activity. Polysaccharide structural features are vital in such activity. Okra ( Abelmoschus esculentus L. Moench) polysaccharides have proven their potency as immune modulators. This study aimed to investigate the structure-dependent immune modulating activity of water-extracted okra ( Abelmoschus esculentus L. Moench) polysaccharide on THP-1 macrophages. Native water-extracted okra polysaccharides (OP) with high molecular weights (>640 kDa) were digested with a polygalacturonase enzyme. Digestion promoted the removal of pectin linear regions (Homogalacturonan; HG), consequently reduced their molecular weight. Digested okra polysaccharides (OPD) were fractionated through size exclusion chromatography to obtain OPDF1 (>640 kDa) and OPDF2 (≤18 kDa). Results revealed all polysaccharide derivatives as nontoxic to THP-1 macrophages. OP-treated THP-1 macrophages increased IL-8, IL-1β, and TNF-α gene expression ( p  < 0.05) compared to unstimulated cells. Immune stimulating activity could not be observed in OPD, OPDF1, or OPDF2. These results indicated that the high molecular weight (MW) and HG associated with Rhamnogalacturonan I (RG-I) are important okra pectic polysaccharide structural features for macrophages stimulation. Highlights: Polygalacturonase enzyme could digest okra polysaccharide into different structures and molecular weights. Both intact and enzymatic digested okra polysaccharide were non-cytotoxic towards THP-1 macrophages. Intact okra polysaccharide displayed immune stimulating activity, but not the enzymatic digested ones.